Surfactant administration in spontaneous breathing with N-CPAP for RDS - Lista, G.; Castoldi, F. (Acta Biomedica Atenei Parmensis, 2014)
Surfactant administration in spontaneous breathing with N-CPAP seems to be a promising approach in the management of neonatal RDS. Both recent RCTs and single centre experience have shown feasibility and good respiratory outcomes with this approach even in extremely preterm infants with respiratory failure. The results of these studies seem to demonstrate that avoiding mechanical ventilation and manual inflation (therefore the risk of high positive pressure and inappropriate tidal volume) it is possible to reduce the risk of VILI and the evolution towards BPD. Further large clinical studies are needed to confirm this hypothesis.